Variasi Pertumbuhan pada ju Keturunan Merbau (Intsia bijuga O.Ktze) di Sobang, banten - Mahfudz Mahfudz; Mohamad Na'iem; Sumardi Sumardi; Eko Bhakti Hardiyanto (Jurnal Pemuliaan Tanaman Hutan, 2010)
The aims of this study to investigate the adaptability, genetic variation of growth character, and genetic correlation among tested plants. The design was Randomized Complete Block Design (RCBD) with 100 tested families from 8 populations, with 4 tree plots and 6 replications. The spacing was 4mx4m. The resultsb showed that adaptabily of plant was very good, with high percentage of plant survival (91.64%). There were significants variations within families and within populations on height, diameter and branching. The individual heritability (h2i)on height and diameter were hight (0.50) and 0.40) and moderate on branching (0,24). The family heritability (h2f) was moderate on height , diameter and branching (0.56, 0.50, and 0.46 respectively). Yhe genetic correlation (rg) between plant heght and diameter was 0.96.